Design and Implementation of PV Poultry Incubator Using PLC - Nithin T Abraham; Shaema Lizbeth Mathew; C.A Pradeep Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
It is very much important to have an improved meathod of poultry incubation because of the increase in demand for chicken. But in conventional meathod of poultry incubation it consumes much power and this power is taken from the grid. In short conventional meathod of egg hatching requires countioous supply of power. Weknow about the increasing demand   In this paper a new meathod of solar poultry incubator design is suggested which could be used to hatch eggs from solar pv and hence could reduce the usage of power and can maximize the usage of solar power which is a renewable source of energy.By implementing this meathod of solar poultry incubator we will be able to reduce the power consumption of the incubator by 75% and the cost involved in the design also yields profit and hence could bring out a reveloution in this field.